2019
DOI: 10.1073/pnas.1900787116
|View full text |Cite
|
Sign up to set email alerts
|

Cochlear partition anatomy and motion in humans differ from the classic view of mammals

Abstract: Mammals detect sound through mechanosensitive cells of the cochlear organ of Corti that rest on the basilar membrane (BM). Motions of the BM and organ of Corti have been studied at the cochlear base in various laboratory animals, and the assumption has been that the cochleas of all mammals work similarly. In the classic view, the BM attaches to a stationary osseous spiral lamina (OSL), the tectorial membrane (TM) attaches to the limbus above the stationary OSL, and the BM is the major moving element, with a pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 45 publications
1
20
0
Order By: Relevance
“…Then we adopted the semi-quantification grading system described by Bernaerts et al (13) to separate vestibular hydrops into four degrees (Bernaerts scores). However, as for the cochlear hydrops, the cochlear endolymphatic expand volume was more than twice the volume of the scala media according to the human cochlear anatomy showed by Raufer et al (26) and according to the calculated results (Table 1). So we separated the hydrops of cochlea into four degrees (Figure 1-cochlea) by adding a degree between normal cochlea and Grade I described by Bernaerts et al because we discovered that for some patients the scala media could expand a bit without forming a round dark circle (Figure 1b).…”
Section: Image Processing Of Mrimentioning
confidence: 62%
“…Then we adopted the semi-quantification grading system described by Bernaerts et al (13) to separate vestibular hydrops into four degrees (Bernaerts scores). However, as for the cochlear hydrops, the cochlear endolymphatic expand volume was more than twice the volume of the scala media according to the human cochlear anatomy showed by Raufer et al (26) and according to the calculated results (Table 1). So we separated the hydrops of cochlea into four degrees (Figure 1-cochlea) by adding a degree between normal cochlea and Grade I described by Bernaerts et al because we discovered that for some patients the scala media could expand a bit without forming a round dark circle (Figure 1b).…”
Section: Image Processing Of Mrimentioning
confidence: 62%
“…The differences highlighted in our study may induce sex-based hearing properties. However, cochlear mechanics in humans are still debated 52 and structure-function relationships within the cochlea should be considered with caution. When compared to other extant and extinct apes, humans have a longer cochlea than expected for their body mass, a proxy indicating a major auditory change that likely occurred in early representatives of the genus Homo approximately 2 million years ago 20 .…”
Section: Discussionmentioning
confidence: 99%
“…Finally, conductive presbycusis corresponded to a gently sloping hearing loss at high frequencies, not reflecting morphological alterations in the sensory cells or stria vascularis but yielding elevated thresholds. This type of presbyacusis might reflect an atypical organization in the organ of Corti that affects its mechanical properties (Motallebzadeh, Soons and Puria 2018; Raufer, Guinan and Nakajima 2019). However, recent results obtained with new techniques developed for histopathological analysis suggested that OHC dysfunction might have been underestimated in age-related hearing loss (Wu et al 2020).…”
Section: Introductionmentioning
confidence: 99%